Ignition process investigation of the gas discharge in the gas-liquid system - Сергеева, Ольга Вячеславовна (Technology audit and production reserves, 2014)
The results of experimental investigations of DC discharge ignition under reduced pressure between the liquid anode and metal cathode are shown. The discharge ignition process for distilled water and prepared solutions is considered. The obtained data will be used in the future to obtain an adequate mathematical description of the processes in the plasma-liquid system. During investigations it is fixed the occurrence of cathode streamer with a deficiency of the charge carriers. It is noted that by using a liquid solution, in which impurities are present, that affect the structural changes in the water, the instantaneous breakdown with a bright flash of discharge ignition occurs at the streamer formation at the anode. The presence of bubbles helps to formation and migration of the charged particles that helps to maintaining a discharge. The obtained data allow a better understanding of the regularities of the plasma-chemical treatment process of liquid environment.